PHOSPHORUS AVAILABILITY IN ALLUVIAL SOIL UNDER DIFFERENT CROPPING SEQUENCES - Maurya, B.M. (Journal of Soil and Water Conservation, 2022)
Intercropping of soybean+pigeonpea in additive and replacement series increased the phosphorus utilization efficiency than its pure cropping, available organic carbon and phosphorus level was increased by inter than sole cropping. Application of phosphorus upto 90 kg P 20 5ha increased the availability of phosphorus after harvest of kharif and rabi crops without having any adverse effect on fertility of alluvial soil.